Innovative cement additives quality improvers in sustainable cement and concrete - Lai, Fook Chuan (Universiti Kebangsaan Malaysia, 2015)
Cement industries globally produced about 2.282 billion ton/year and 25 billion tons of concrete are produced yearly all over the world, necessary measures are to be taken to reduce energy use along with the prevention of environmental degradation, depletion of the limited resources and contribute 7% to global warming effects due to the release of carbon dioxide to the atmosphere. Cement additives quality improver polymer (CAQIP) was developed from synthesized polymer, waste materials derived from petro-chemical and palm oil waste for production of sustainable cement. Industrial scale trial in a local cement plants by dosing 0.009%-0.690% CAQIP significant improved productivity, 8.3-27.5% efficiency in saving, 24.73-86.36% clinkering energy and 7.7-21.57% grinding energy in the production of Ordinary Portland Cement and sustainable cement. Strength quality improved 7.31-34.8% (2 day) and 3.85-57.58% (28 day). Carbon dioxide and others toxic gases emission was reduced 21.90-90.0% by replacing clinker with waste material such as fly ash (25-35%), out-spec clinker (50-100%) and limestone waste (5-25%). The developed CAQIP significant improved productivity, quality strength, reduced CO2 emission, grinding & clinkering energy and enhanced production of sustainable cement and concrete in Malaysia.